2022
DOI: 10.1038/s41467-022-32679-1
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine dissociates methylphenidate effects on value-based versus surprise-based reversal learning

Abstract: Psychostimulants such as methylphenidate are widely used for their cognitive enhancing effects, but there is large variability in the direction and extent of these effects. We tested the hypothesis that methylphenidate enhances or impairs reward/punishment-based reversal learning depending on baseline striatal dopamine levels and corticostriatal gating of reward/punishment-related representations in stimulus-specific sensory cortex. Young healthy adults (N = 100) were scanned with functional magnetic resonance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 112 publications
1
10
0
Order By: Relevance
“…Critically, the absence of correlations was not due to measurement error in the estimates of striatal dopamine synthesis capacity or a lack of behavioural relevance of these estimates. The striatal [ 18 F]-FDOPA uptake values are in the typical range (Supplementary Figure 1), and dopamine synthesis capacity in this dataset has been shown to account for (dopamine drug effects on) effort-based decision making, response vigour, reversal learning, and smartphone social activity in the expected direction (Hofmans et al, 2020, 2022; van den Bosch et al, 2022; Westbrook et al, 2020, 2021). More specifically, [ 18 F]-FDOPA uptake in the striatum was associated positively with the value of cognitive effort (Westbrook et al, 2020), with the impact of average reward value on response vigour (Hofmans et al, 2022) and with dopaminergic drug-related changes in prediction error-related BOLD signal in the striatum (van den Bosch et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Critically, the absence of correlations was not due to measurement error in the estimates of striatal dopamine synthesis capacity or a lack of behavioural relevance of these estimates. The striatal [ 18 F]-FDOPA uptake values are in the typical range (Supplementary Figure 1), and dopamine synthesis capacity in this dataset has been shown to account for (dopamine drug effects on) effort-based decision making, response vigour, reversal learning, and smartphone social activity in the expected direction (Hofmans et al, 2020, 2022; van den Bosch et al, 2022; Westbrook et al, 2020, 2021). More specifically, [ 18 F]-FDOPA uptake in the striatum was associated positively with the value of cognitive effort (Westbrook et al, 2020), with the impact of average reward value on response vigour (Hofmans et al, 2022) and with dopaminergic drug-related changes in prediction error-related BOLD signal in the striatum (van den Bosch et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
“…The striatal [ 18 F]-FDOPA uptake values are in the typical range (Supplementary Figure 1), and dopamine synthesis capacity in this dataset has been shown to account for (dopamine drug effects on) effort-based decision making, response vigour, reversal learning, and smartphone social activity in the expected direction (Hofmans et al, 2020, 2022; van den Bosch et al, 2022; Westbrook et al, 2020, 2021). More specifically, [ 18 F]-FDOPA uptake in the striatum was associated positively with the value of cognitive effort (Westbrook et al, 2020), with the impact of average reward value on response vigour (Hofmans et al, 2022) and with dopaminergic drug-related changes in prediction error-related BOLD signal in the striatum (van den Bosch et al, 2022). The implication of this body of work is that more sophisticated and quantitative indices of value-based learning, motivation, and even daily logs of participants’ social activity on their smartphone might be better proxy measures of striatal dopamine synthesis capacity than the simple trait measures reported here.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…On their first visit (day 1), participants were screened for eligibility, in part based on medical and psychiatric interviews, and completed assessments of WM capacity; listening span (Daneman & Carpenter, 1980; Salthouse & Babcock, 1991), digit span (Groth-Marnat et al, 2000), and crystallized intelligence (Crawford et al, 1989; Schmand et al, 1991), and also providing measures of spontaneous eye blink rate (electrooculography), and an anatomical brain scan. The screening session was followed by pharmacological-fMRI sessions on day 2–4, which are reported elsewhere (van den Bosch, Lambregts, et al, 2022). On the final visit, in addition to the PIT task, participants completed a second Digit Span Test and a fluid intelligence assessment; Wechsler Adult Intelligence Scale, 4th edition, Dutch edition (Wechsler, 2008), followed by an [ 18 F]-DOPA PET scan to establish participants’ K i .…”
Section: Methodsmentioning
confidence: 99%
“…The data reported here were acquired in the context of a larger pharmacological PET/fMRI study, components of which have been and will be reported separately (Hofmans et al, 2020(Hofmans et al, , 2022Määttä et al, 2021;van den Bosch, Hezemans, et al, 2022;van den Bosch, Lambregts, et al, 2022;Westbrook et al, 2020; an overview of the complete study at https://osf.io/d3h8e). For this study, participants paid five visits.…”
Section: General Proceduresmentioning
confidence: 99%